Persistent organochlorine pesticides and polychlorinated biphenyls in intensive agricultural soils from North India - Bhupander KUMAR; Sanjay KUMAR; Richa GAUR; Gargi GOEL; Meenu MISHRA; Satish Kumar SINGH; Dev PRAKASH; Chandra Sekhar SHARMA (Soil and Water Research, 2011)
Organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs) were determined in agricultural soils from the northern states of India. The average concentration of OCPs was 37.67 ± 0.33 ng/g (dry weight - DW) while HCHs alone accounted for 93% followed by DDT (4.27%) and endosulphan (2.51%). The α/γ ratio of HCH (< 0.01-8.64) reflects the use of technical as well as lindane formulations. The ratio of p,p'-DDT/p,p'-DDE (0.16) and o,p'-DDT/p,p'-DDT (< 0.01) indicates the contamination of soils with the past use of technical DDT. The mean concentrations of endosulphan and dieldrin were 0.95 ± 0.53 ng/g (DW)and 0.16 ± 0.07 ng/g (DW), respectively. The average concentration of PCBs was 13.44 ± 0.06 ng/g (DW). The toxic equivalency (TEQ) calculated using WHO 2005-TEFs ranged from 0.01 to 105.40 pg WHO 2005-TEQ/g (DW) with the mean of 13.78 ± 0.11 pg WHO 2005-TEQ/g (DW). PCB-105 (25%), PCB-114 (18%), and PCB-118 (18%) were the dominant congeners and accounted for 61% while a non ortho PCBs contributed only 18% to total DL-PCBs. The contamination of soils is a matter of concern but is not alarming because the observed levels were lower than those given by the Canadian soil quality guidelines.